1934 Ky. Acts 169-70 - (:unkn) unknown (My University, 1934)
An Act . . . prescribing punishment for robbery or burglary . . ., ch. 52,§ 1159(a): That if any person shall commit acts of robbery, burglary . . . robbery of bank [sic] or safe, and in committing said act or acts shall use or display any pistol, gun or other firearms or deadly weapon of any character in so doing; upon conviction such person or persons shall be sentenced to death or life imprisonment in the discretion of the jury
Keywords: COMMITTING CRIME W/ WEAPON